Efek Mediasi Implementasi Social Sustainability Terhadap Kinerja Perusahaan di Masa Pandemi Covid-19 - Bowie Prasetyo; Sumarsono Sudarto (Universitas Mercu Buana, 2022)
This study aims to examine the mediating effect of the implementation of Social Sustainability on the manufacturing supply chain to find the right model for resilience to future economic disasters. This study took data as a sample of 150 respondents from all 160 companies in supply chain that were able to survive during the pandemic. Using the variables Management Commitment and Financial Support as well as SEM-PLS tools to test the hipothesis of a direct or indirect relationship to company performance. The research findings indicate that the effect of the Financial Support variable on Company Performance was initially positive and significant in a direct relationship, turned insignificant if there was a Social Sustainability implementation variable as a mediating variable. Same things are shown in the influence of the Management Commitment variable on Company Performance. This finding can be the first step of research on the implementation of Social Sustainability in Indonesia which is still very rarely done and illustrates that during the pandemic when this research was conducted, the focus of the company was to survive the impact and respondent considered the implementation of Social Sustainability to have a negative impact and burden the company’s finances and Performance.